PENGARUH ONLINE CUSTOMER REVIEW DAN CUSTOMER RATING TERHADAP KEPERCAYAAN KONSUMEN DAN KEPUTUSAN PEMBELIAN MAKE OVER PADA MARKETPLACE SHOPEE DI KOTA SEMARANG - Wiharti Dwi Ovaliana; Mahfudz Mahfudz (Faculty of Economics and Business Diponegoro University, 2022)
Increasing awareness among women in Indonesia regarding the appearance of cosmetics in Indonesia has increased demand. This demand for cosmetics is also supported by increasingly sophisticated technological improvements. This technological improvement is able to change consumer habits from shopping offline to online. This study was conducted to examine the effect of customer reviews and customer ratings on trust and purchasing decisions. The sample data used in this study were 110 respondents of consumers of Make Over beauty products in the city of Semarang. The sampling technique used is a non-probability sampling technique with a purposive sampling approach. The data analysis technique used is SEM with the AMOS 24.0 application. The results showed that all hypotheses one to five had positive and significant results. All hypotheses have CR > 1.96 and p value 0.05. Online customer reviews have a positive and significant impact on consumer trust, customer ratings have a positive and significant impact on consumer trust, online customer reviews have a positive and significant impact on purchasing decisions, customer ratings have a positive and significant impact on purchasing decisions, and consumer trust has a positive and significant impact on purchasing decisions. positive and significant influence on purchasing decisions.